Physical processes of soil in Pedregal de San Angel ecological reserve: attributes for conservation. - Castellanos Vargas, Iván; García Calderón, Norma E.; Cano Santana, Zenón (REVISTA TERRA LATINOAMERICANA, 2017)
The Pedregal de San Angel Ecological Reserve at Ciudad Universitaria (PSAER-CU) has a fraction of the original lava spill of Xitle volcano and currently the soil and plant community are affected by the landscape fragmentation, construction waste filler (such as rubble and other materials) and irregular constructions. A description of the main physical properties of soil in sites with contrasting topography (open preserved and disturbed planes, rifts and hollows) was made. A significant effect of topography on edaphic properties was found. Organic matter fraction showed positive correlations with the percentages fractions of porosity, clay and moisture, and also showed negative correlations with the bulk and particle densities values, compaction, acidity and sand content. The percentage of organic matter was the most important attribute for the analysis classification of sites. The disturbed open plots followed a different edaphogenic path from the conserved sites and resembled Urbanosols. It is suggested the implementation of strategies aimed at achieving its ecological restoration. The soil classification corresponds to three probable orders: 1) Haplic Entisol by the recent geological age of deposition and currently underway pedogenesis processes; 2) Lavic Lithosol by the recurrence of magmatic rock outcrops and 3) Vitric Andosol by the nature of the parent material and textural predominance of sands. It is concluded that the soil of the PSAER-CU is incipient and currently the diagnostic horizons are in development process. Soil environmental importance lies in its capacity of water filtration and retention; its porosity and compaction allow it to be a seed bank and habitat of diverse insect species. Fragility of edaphic aggregates and the textural predominance of sand represented a latent erosion factor.